Analisis Kinerja Keuangan Bank Muamalat Indonesia Periode 2020-2024 Berdasarkan Metode RGEC: Studi Pasca Akuisisi BPKH - Asrifah, Dini; Miftahur Rahman; Septian Fiktor Riyantoro (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
Academic concerns arise from Bank Muamalat Indonesia (BMI) financial performance pressures due to Covid-19 pandemic, global economic turmoil, and intense sharia banking competition, destipe OJK regulations and BPKH acquisition worth Rp 5 trillion in 2023. This study aims to analyze BMI’s health level from 2020-2024 using RGEC method and compare changes pre- and post-acquisition. Descriptive quantitative method employs secondary data from BMI’s audited annual reports (purposive sampling), analyzed through ratios; NPF, FDR, GCG self-assessment, ROA, ROE, BOPO, and CAR. Results reveal healthy risk profile (average NPF 2,47%, FDR very healthy rank 1-2), stable GCG (rank 2-3), very healthy capital (average CAR >25% rank 1), but weak earnings (ROA/ROE <0,5%, BOPO >96% rnak 4-5). BPKH acquisition effectively strengthens capital and reduces credit risk exposure. Implications recommend BMI pursue cost restructuring, digitalization, and sharia financing expansion for sustainable profitability enhancement.